PROBLEMS IN THE FAMILY AND THE URGENCY OF FAMILY COUNSELING IN TODAY - Suhartiwi, Suhartiwi; Neviyarni, Neviyarni; Syukur, Yarmis (Bisma The Journal of Counseling, 2019)
Problems in the family become an issue that is always discussed in the development of psychological science and counseling. The family as a place to protect, be compassionate, build themselves up for its members often causes many problems. The problem is related to interactions between family members so that it causes conflict. This paper was written using the literature review method. The findings show that interactions that occur within families vary and are prone to conflict. So it is very important for family counseling to handle and develop a family to become a healthy and harmonious family.